(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the national-cultural identity of the concepts of the semantic field of "food" based on materials from modern American English. The article presents the main views on the nature of the concept in linguistics; the roots of the use of “gastronomic” vocabulary in mythology and folk oral creativity are analyzed. On the basis of large-scale factual materials, the activities of culinary terms, the content and structure of the concepts behind them and the role of these concepts in the transmission of ethnopsychology information are studied. We will consider the problem of reflecting the peculiarities of national culture in the concepts of the semantic field "food", presented in artistic and publicist texts as a product of this culture, which we will analyze mainly on the materials of English-language texts that represent modern America.